Analisis Kinerja Keuangan Pt. Bni (Persero) Tbk Sebelum Dan Sesudah Melakukan Seasoned Equity Offerings - Nancy Ika Ervina, ; Musdholifah, (Bisnis dan Manajemen, 2010)
Seasoned equity offering (SEO) is done by public company which need seasoned loan to costing operational activities and invest. Except to costing operational activities and invest a company, this offering can used to looking for seasoned loan to pay company loan. The aim of this study is to analyze financial performance of PT. BNI (Persero) Tbk before and after seasoned equity offering (SEO) with CAMELS (Capital, Assets Quality, Management, Equity, Liquidity, dan Sensitivity) measurement. This research represent descriptive which purposed to collect information about exist symptom. This research is done in PT. BNI (Persero) Tbk. Ratio analysis are using Capital : CAR, Assets Quality : KAP1 dan KAP2, Earning : ROA dan BOPO, Liquidity : NCM to CA dan LDR, which later from the ratio can be explained its meaning. The conclusion of this research that financial performance PT. BNI (Persero) Tbk generally before seasoned equity offering (2006) is better than after seasoned equity offering (2008) which is in first period (January March), second period (April June), and third period (July September). Therefore in fourth period (October - December) 2008, financial performance PT. BNI (Persero) Tbk is better than 2006.